Kampung Adat Dari Perspektif Ketatanegaraan Republik Indonesia - Bauw, Lily (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
This research reveals that the pattern of government administration and the formation of traditional villages is carried out by respecting the value system that applies to society. This is in line with the 1945 Constitution of the Republic of Indonesia which emphasizes that the state recognizes and respects customary law community units and their traditional rights as long as they are still alive and in accordance with the development of society and the principles of the Unitary State of the Republic of Indonesia. The existence of Traditional Villages is the need of the people in Papua Province for the establishment of traditional villages, especially related to providing recognition for the rights of traditional law communities which have so far been neglected based on several facts, as follows: first: the customs and culture of indigenous Papuan people have great diversity. differences between one ethnic group and another, including aspects of language, political system, religion and belief. Therefore, Regional Governments need to pay attention to clear regulations regarding the implementation of regional government as a driving force for regional autonomy by using the principles of decentralization, assistance tasks and deconcentration. In the administration of regional government, there are several rights that regions have, namely (1) the right to regulate and manage their own government affairs, (2) elect regional leaders, (3) manage regional apparatus, (4) manage regional assets, (5) collect regional taxes and levies. regional, (6) receive profit sharing from the management of natural resources and other resources in the region, (7) obtain other legitimate sources of income, and (8) obtain other rights regulated in statutory regulations.